LIMBAH ANORGANIK SEBAGAI IDE PENCIPTAAN SENI KRIYA SMA WAHYU MAKASSAR - Andi Andini Arif Paturusi; Irsan Kadir; Soekarno Buchary Pasyah (Program Studi Pendidikan Seni Rupa Fakultas Keguruan dan Ilmu Pendidikan Universitas Muham, 2023)
This research utilizes inorganic waste, namely used plastic that is no longer used, it is hoped that in the future the art of craft from anorgnaik waste can reduce the amount of waste that is an obstacle at this time. The purpose of this study was to determine the planning, implementation and results of making decorative lamps from inorganic waste in Class X Students of SMA Wahyu Makassar. Collection techniques through observation, interviews and documentation. The results of the study provide results where Class X students of SMA Wahyu Makassar are able to know the materials and tools to be used and are able to work on decorative lamps in accordance with the design design that has been designed. The results of the decorative lamps produced are very good and have high artistic value so that they can be used as displays at home or anywhere. The results of interviews with both teachers and students provide answers that the art craft learning process starts from good planning and students can work on artwork well and enthusiastically.